Fitness limitations in non‐disabled extremely low birthweight adolescents. Issue 7 (11th June 2013) - Danks, Marcella; Burns, Yvonne R; Gibbons, Kristen; Gray, Peter H; O'Callaghan, Michael J; Poulsen, Leith; Watter, Pauline
<x xml:space="preserve">Abstract</x> Aim This study aims to compare non‐disabled otherwise healthy extremely low birthweight (ELBW) (<1000 g) children and term‐born peers in an investigation of relationship between cardiorespiratory endurance and parent report of competence. Methods Forty‐eight of 105 eligible ELBW 11‐ to 13‐year‐old children (27 male) and 55 term‐born school peers (28 male) completed a 20‐m shuttle run, anthropometric measures, respiratory function tests and the Motor Assessment Battery for Children. Parents completed the Child Behavior Checklist (CBCL). Results The ELBW group had poorer cardiorespiratory endurance (P = 0.002), growth (P = 0.002), respiratory function (P = 0.003) and motor ability (P < 0.001) than term‐born peers. Parents reported the ELBW children to be less competent than term‐born peers: CBCL total T score mean difference −9, 95% confidence interval −14, −5 (P < 0.001). Cardiorespiratory endurance predicted competence (regression coefficient 0.865; 95% confidence interval 0.352, 1.378; P = 0.001) independent of prematurity, growth, respiratory function, motor score, gender and socio‐economic status. Cardiorespiratory endurance had association with social competence for all participating children, but was related to CBCL Activities Competence only for the ELBW children who were the significantly less fit group. Conclusions The poor cardiorespiratory endurance prevalent in non‐disabled otherwise healthy ELBW children is associated with general competence independent of prematurity and of the impact of other mild physical deficits, gender or socio‐economic status. The relationship demonstrated between cardiorespiratory endurance and competence to engage in general activities of daily living, seen only in the less fit ELBW children, identifies the fitness levels in non‐disabled ELBW children as a barrier to participation.